Assessment of Belg 2023 Climate and Climate Outlook of the upcoming Kiremt 2023 - Teshome, Asaminew; Demissie, Teferi Dejene (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
In collaboration with AICCRA, EMI held a workshop to present the assessment of the Belg 2023 climate and the outlook of the upcoming Kiremt 2023. It was held within the NFCS-E framework, mainstreaming climate into key socio-economic sectors for resilience and sustainable development. It was convened on May 16, 2022, at Haile Resort, Adama, Ethiopia, and brought together 300 government officials of WoWE, EDRMC, EMI, representatives from socio-economic sectors, international partners, civic societies, and media. Three important sessions took place at the workshop. In the opening session, the opening remark was delivered by Mr. Fetene Teshome, Director General of EMI; Dr. Teferi Demissie from AICCRA and Dr. Mariane from WMO RA1 delivered keynote speeches; finally, opening remarks were delivered by H.E Dr. Eng. Habtamu Etefa Minster of MoWE. Presentations on AICCRA, Belg 2023 assessment, and the climate outlook of Kiremt 2023 were entertained during the second session. In the last session (parallel breakout session), participants were divided into two groups to discuss and present the socio-economic impact assessments of Belg 2023 and the potential impacts of Kiremt 2023 on health, water, energy, environment, and disaster risk reduction.